Corporate governance and value-relevance of accounting information of listed hotels and travels in Sri Lanka / Saseela Balagobei - Balagobei, Saseela (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2018)
Today corporate governance has become a global issue and the development of corporate governance practices is considered to be a prominent theme all over the world. This study aims to investigate the impact of corporate governance on the value relevance of accounting information of listed hotels and travels in the Colombo Stock Exchange. Twenty listed companies were analyzed for a period of five years from 2012 to 2016. Corporate governance is measured by board size, board independence and ownership structure whereas EPS and net assets value per share were considered as the variables of value relevance of accounting information. Data was collected from the annual reports of the listed companies, magazines and scholarly articles from academic journals. Correlation and multiple regressions were used to analyze and evaluate the collected data. The results reveal that board independence and ownership structure have a significantly negative influence on value relevance of accounting information of listed hotels and travels in Sri Lanka while firm leverage has a negative influence on value relevance of accounting information. Therefore, firms with strong corporate governance practices exhibit a higher value- relevance of accounting information.